EFFECT OF FINANCIAL LITERACY, RISK PERCEPTION, AND FINANCIAL ATTITUDE ON INVESTMENT DECISIONS OF MILLENNIAL GENERATION - Desiyanti, Rika; Islamiati, Febi; Fitria, Reza; Moreno, Kiko; Sari, Julia Novita (Jurnal Apresiasi Ekonomi, 2025)
This study aims to determine and analyze the influence of financial literacy, risk perception, and financial attitudes on the investment decisions of the millennial generation of Bung Hatta University students. The variables studied include financial literacy (X1), risk perception (X2), and financial attitudes (X3) as independent variables, and investment decisions (Y) as the dependent variable. The population in this study were Bung Hatta University students, class of 2021-2023. The sample taken was 204 respondents using the Proportionate Stratified Random Sampling method. The analysis technique used is Smart PLS 3. The results of this study indicate that financial literacy has a positive effect on investment decisions, risk perception has a positive effect on investment decisions, and financial attitudes have an effect on investment decisions.